Study of Control Strategy and Parameter-design for Grid-side Converters of 2.5 MW Wind Power Generation System - SUN Lu; ZHANG Zhixue (Kongzhi Yu Xinxi Jishu)
It studied a control strategy for grid-side converters of 2.5 MW wind power generation system, presented a method for parameters design of LCL filter and introduced points of harmonic detection methods for grid voltage. Simulation and experimental results verify the feasibility of the control strategy and show that it can achieve the expected design results with the parameter-design.